ПРО РОЛЬ ГІРНИЧО-ГЕОЛОГІЧНИХ УМОВ І ФІЗИКО- ХІМІЧНИХ ФАКТОРІВ ПРИ ФОРМУВАННІ ГАЗОНАСИЧЕНОСТІ ВУГЛЕПОРОДНИХ МАСИВІВ ДОНЕЦЬКО-МАКІЇВСЬКОГО ВУГЛЕПРОМИСЛОВОГО РАЙОНУ - Yevdoshchuk, М.; Vergelska, N.; Krishtal, А. (Institute of Geological Sciences of the Ukrainian National Academy of Sciences, 2013)
The main part of coal rock massifs is characterized by presence of small-amplitude faults in the Donetsk-Makiivka coalmine district that represented by shear zones genetically linked to strike-slip faults resulting in gas dynamic phenomena manifestations. Morphological peculiarities of the strike-slip faults and structural paragenesis of shear zones with gas saturation of the coal rock massifs in the Donetsk-Makiivka coalmine district are recognized.